Heavy Metal(loid) Accumulation in the Ovarian Tissue of Free-Ranging Queens and Bitches Inhabiting Highly Polluted Urban Environments - Giovanni Forte; Federica Ariu; Beatrice Bocca; Giuliana Solinas; Giovanni Giuseppe Leoni; Andrea Podda; Roberto Madeddu; Luisa Bogliolo (Animals, 2023)
There is strong scientific evidence that exposure to environmental contaminants, such as heavy metal(loid)s (HMs), can impair female reproductive function. Pets, such as cats and dogs, who share the same habitat as humans, may be particularly useful sentinel models for detecting HMs in the ovary. In the present study, we compared the concentration of essential (Ems; Cu, Fe, Mn, Se, and Zn) and non-essential metal(loid)s (NEMs; Al, As, Cd, and Pb) in the ovarian tissues of free-ranging queens and bitches of different ages living in industrialized/highly polluted (south group) and non-polluted (north group) urban areas of the island of Sardinia, Italy. The results showed that both EMs and NEMs were present at detectable concentrations in feline and canine ovaries and their levels varied according to geographical areas and animal age. Among the EMs, Cu was found elevated in older queens and bitches inhabiting the southern area. Cadmium and lead were higher in feline and canine ovaries of older animals from the south compared to those living in the north. In addition, Cd and Pb concentrations increased in individuals of both species living in the south. These findings showed new perspectives for the use of pets as early warning sentinels of environmental pollution by HMs and for the risk of human exposure within a “One Health” approach. Pets may help to study the link between exposure to metals and female reproductive disturbances in mammals.